A protocol guided by transpulmonary thermodilution and lactate levels for resuscitation of patients with severe burns - Berger, Mette M (BioMed Central, 2013)
Over-resuscitation is deleterious in many critically ill conditions, including major burns. For more than 15 years, several strategies to reduce fluid administration in burns during the initial resuscitation phase have been proposed, but no single or simple parameter has shown superiority. Fluid administration guided by invasive hemodynamic parameters usually resulted in over-resuscitation. As reported in the previous issue of Critical Care, Sánchez-Sánchez and colleagues analyzed the performance of a ‘permissive hypovolemia’ protocol guided by invasive hemodynamic parameters (PiCCO, Pulsion Medical Systems, Munich, Germany) and vital signs in a prospective cohort over a 3-year period. The authors’ results confirm that resuscitation can be achieved with below-normal levels of preload but at the price of a fluid administration greater than predicted by the Parkland formula (2 to 4 mL/kg per% burn). The classic approach based on an adapted Parkland equation may still be the simplest until further studies identify the optimal bundle of resuscitation goals.